Measurements of binding energies and electromagnetic moments of silver isotopes – A complementary benchmark of density functional theory - R.P. de Groote; D.A. Nesterenko; A. Kankainen; M.L. Bissell; O. Beliuskina; J. Bonnard; P. Campbell; L. Canete; B. Cheal; C. Delafosse; A. de Roubin; C.S. Devlin; et al. (Physics Letters B, 2024)
We report on a set of high-precision measurements of nuclear binding and excitation energies, as well as nuclear spins, magnetic dipole and electric quadrupole moments of neutron-rich silver isotopes, 113−123Ag. The measurements were performed using the JYFLTRAP mass spectrometer and the collinear laser spectroscopy beamline at the Ion Guide Isotope Separator On-Line (IGISOL) facility. For the first time, we can firmly establish the ordering of the long-lived Iπ=1/2−,7/2+ states in these isotopes, and pin down the inversion of these two levels at either A=121(N=74) or A=123(N=76). We compare these findings to calculations performed with density functional theory (DFT), from which we establish the crucial role that the spin-orbit strength and time-odd mean fields play in the simultaneous description of electromagnetic moments and nuclear binding.